Organizational change: a transition model (Research, Society and Development, 2020)
The article continues the development of the literature on the Strategic Business Units (SBU). In order to fill in the gaps on that subject, an explanatory research was carried out on the theme in the context of Organizational Changes (OC); developing a model that was initially dedicated to guiding traditional organizations that aspire to adopt the SBU-based corporate management philosophy. In order to make the tool robust, during its creation, several studies related to strategic changes in organizations were studied, as well as frequent errors in the management process of these changes and critical success factors that help in the absorption and subsequent solidification of the transformations proposed by the leadership business. Such issues were so carefully considered in the definition and organization of the stages of the model, that it provided the creation of a tool that goes beyond its initial objective - that is - to assist companies that demand to adopt the philosophy by Business Units, giving shape to a pattern that may be used to enable any type of strategic change in organizations: the DP-ACS.